Consent of The Bride and Groom from A Gender Perspective: Comparative Study of The Books of Kanz Al-Ragibin and Al-Mar'ah Fi Al-Hadarah Al-Islamiyyah - Amin, Muhammad Fikri Amin; Mesraini, Mesraini; Dahlan, Abdurrahman (STAINI Press, 2026)
The consent of the bride and groom is one of the issues still being discussed in Shafi'i fiqh. This study examines the issue of spousal consent in two books from different eras. The book Kanz al-Ragibin is a classical Shafi'i fiqh text written by al-Mahalli, while the book Al-Mar'ah fi al-Hadarah al-Islamiyyah is a contemporary Shafi'i text written by Ali Jum'ah. This research method is qualitative in nature, using a gender approach, with the selected perspective being Islamic Gender. Data collection techniques involve interviews and documentation studies. The results of this study indicate that, according to al-Mahalli, the consent of the bride and groom is not a valid requirement for marriage, whereas according to Ali Jum’ah, the consent of the bride and groom is a requirement that must be considered in marriage. This difference stems from the existence of the right of ijbar. The right of ijbar existed and was implemented during al-Mahalli’s time, whereas during Ali Jum’ah’s time, it was not widely implemented. Nevertheless, both share the same legal principle that a father will protect his child. Al-Mahalli uses the concept of mafhûm al-mukhâlafah in the hadith “al-tsayyib ahaqqu bi nafsihâ min waliyyihâ,” while Ali Jum’ah uses a textual understanding (mantûq) of the hadith. Additionally, during Al-Mahalli's time, women tended to be socially passive in public, often staying at home without interacting with any men. In contrast, during Ali Jum'ah's time, women had more freedom in public spaces. They achieved legal equality in almost all aspects. When viewed from a gender perspective, the opinions of al-Mahalli and Ali Jum’ah align with the concepts of justice and gender equality of their respective eras. This study also indicates that Ali Jum’ah’s perspective on the consent of both spouses reflects a progressive legal approach that is appropriate as a reference and guideline for contemporary marriage.